Hubungan antara Promosi Kesehatan dan Keselamatan Kerja dengan Tindakan Pencegahan Covid-19 Pada Pegawai Rumah Sakit - Veronica Waleleng; Diana Vanda D. Doda; Aaltje Ellen Manampiring (Sam Ratulangi Journal of Public Health, 2020)
Background: Indonesia is currently experiencing a case of the Covid-19 pandemic, a case of the corona virus appears and attacks humans for the first time in Wuhan Province, China. This emergency occurs mainly in patients with previous health problems. Many schools and universities are closed by the government by imposing learning and working at home, limiting religious activities, limiting transportation modes, restricting activities in public places and dismissing workplaces and other activities specifically related to aspects of defense and security. The government in this case continues to make promotions to disseminate the prevention of the spread of the corona virus, especially in workplaces. Health promotion is an important determinant of the healthy behavior of the community, especially workers who continue to work during the Covid-19 pandemic. The purpose of this study was to analyze the relationship between Occupational Health and Safety Promotion (K3) and COVID 19 Prevention Measures for employees at a hospital in North Sulawesi Province. Methods: This study was an observational study with a cross sectional study design. The population in this study were all employees of the Eye Hospital. The sample in this study was a total population of 70 people. The independent variables in this study were training, communication, and supervision with the dependent variable, namely the prevention of Covid 19. The research data were analyzed using univariate, bivariate and multivariate analysis and chi-square statistical calculations. Presentation of data is made in table and narrative form. Results: This study showed that 51.8% of hospital staff did not take preventive measures properly. The results of the bivariate analysis showed that there was a significant relationship between K3 training and covid-19 preventive measures with a value of p = 0.047, there was a significant relationship between K3 communication and covid-19 prevention measures with a value of p = 0.000, there was a significant relationship between supervision and covid-19 precaution with a value of p = 0.000. The results of the multivariate analysis showed communication (p = 0.000; OR = 5.090 was the most dominant influencing factor, with good supervision it would increase covid-19 prevention measures for employees at a hospital in North Sulawesi Province, Conclusion: Conclusion of the study This states that OHS training, OHS communication and supervision have an important role in efforts to prevent Covid-19 at a hospital in North Sulawesi Province and the factor that plays the most role in taking Covid 19 preventive measures is K3 communication.